Comparative Analysis of Cytotoxicity and Odontogenic Differentiation of Novel Bioceramic Material on Human Dental Pulp Stem Cells – An In Vitro Study - G. R. Ishwarya Dhevi; Ponnudurai Arangannal; J Jeevarathan (Journal of Pharmacy and Bioallied Sciences)
Background and Objective: Bioceramic materials have revolutionized the field of endodontics by successfully transforming the outcomes of pulp therapies. Novel biomaterials are evolving by modifying the conventional mineral trioxide aggregate (MTA) to overcome their existing limitations, the major ones being prolonged setting and cytotoxic radiopacifiers. Dental white portland cement (DWPC) is a novel formulated bioceramic material introduced as an enhanced MTA alternative. This in vitro study aims to investigate the cytotoxicity and odontogenic differentiation of novel formulation DWPC with MTA Angelus, Biodentin (BD) and white portland cement (WPC) on human dental pulp stem cells (HDPSCs). Materials and Methods: HDPSCs were cultured in Dulbecco’s modified eagle’s medium (DMEM) with fetal bovine serum (FBS) and antibiotics at 37°C, 90% humidity in a 5% CO2 incubator. Experimental samples were prepared as disks. The viability of HDPSCs was measured by Mosmann’s tetrazolium toxicity (MTT) assay, and odontogenic potential was assessed using alkaline phosphatase (ALP) activity at 24 hours, 7-, 14-, and 21-day intervals. The mean and standard deviations were statistically analyzed by one-way ANOVA and post hoc Scheffe tests using IBM SPSS Software (IBM statistical package for social sciences) – Version 24.0 with a significance level set as P < 0.05. Results: All four groups tested using MTT assay showed no toxicity and possess odontogenic potential in all the experimental durations. Experimental group DWPC presented with the highest mean cell viability and ALP activity at all intervals followed by WPC, MTA, and BD (P < 0.05). Conclusion: DWPC presented good bioactivity in terms of cell viability and ALP activity. Thus, DWPC could be a promising endodontic material. However, further research is warranted to explore the clinical applicability.